Mr. Singer's seamstress : [large type] a Washington Territory story - Stover, Karla Wakefield (WHEELER PUBLISHING LARGE PRINT Softcover Western, 2023)
"In 1882, less than ten years after the Northern Pacific Railroad established a terminus on Commencement Bay and helped create a city called New Tacoma, the community is thriving. Stores, stables, a new hospital, and the beginnings of a hotel to rival San Franciscos Cliff House are going up. In town, horse-drawn street cars are pulled on gravel roads, and there is even the beginning of a new telephone system. In Nell Tanquists opinion, the town has everything it needs to rival nearby Portland-almost everything, that is, except a dress-making establishment. Nell wants to create clothes for beautiful women and clothes to make plain women look beautiful, but sewing by hand will only take her so far, and the one thing she lacks to become a proper dressmaker is a sewing machine. To earn money, she works at any job that comes her way; taking an uncomfortable and unforgettable wagon ride to nearby Steilacoom to sell things shes crocheted; serving punch at what begins as an elegant "at-home" party that turns into something less than genteel; and working at the Halstead Hotel. As welcome summer weather warms the town, she also finds time for fun-taking her sister to the pantomime and going to a tea party, and for a romance that threatens to scuttle her dream. A picnic with her friends on Commencement Bay nearly turns deadly, and an attempted kidnapping she witnesses on a dark and rainy night takes her into uncharted territory. Mr. Singers Seamstress is full of pioneers, Chinese laborers, and members of the Puyallup Indian tribe-all people who settled New Tacoma. Most of all, though, its Nells story: the story of a girl determined to buck convention and follow her own path""--